The incidence of AmpC β-lactamases producing Klebsiella pneumoniae subspecies pneumoniae - Singh, Priyanka (International Journal of Research in Medical Sciences, 2018)
Background: AmpC β- lactamases in the clinical isolates reduces the therapeutic value of β- lactam- β-lactam inhibitor combinations. if not detected can be disseminated in the hospital environment and pose a serious therapeutic challenge. Hence present study is undertaken to detect the incidence of AmpC β -lactamases producing Klebsiella pneumoniae subspecies pneumoniae out of total 300 Klebsiella pneumoniae subspecies pneumoniae isolated from different clinical samples of the patient attending Jawaharlal Nehru Medical College and its hospital in Dept of Microbiology. Methods: Isolates are screened for presumptive AmpC production by testing their susceptibility to Cefoxitin using Kirby-Bauer disk diffusion method. Phenotypic confirmatory tests for detection of AmpC β- lactamases by Modified three dimentional test, Amp C disc test, Amp C disc test with Inhibitor (Boronic Acid) based disc potentiation test. Results: In our present study 75 (25%) Klebsiella pneumoniae strains were positive for AmpC β lactamases production either alone or in combinations with other β- lactamases. 75 strains were positive for AmpC β-lactamase (25%). These 75 strains were further confirmed by E Test. Conclusions: Overproduction of AmpC β- lactamases by mutation is responsible for resistance. if not detected can be pose a serious therapeutic challenge. So, its detection improves the therapeutic outcome in patient care.